Problems and Prospects of Bangladesh Islamic Library Network: a Case Study of Bangladesh Islamic University and Islamic Foundation Library - Muhammad Mezbah-ul Islam; Md. Golam Mostafa; Md. Anwarul Islam (Universiti Sains Islam Malaysia, 2024)
Presenter from Department of Information Science & Library Management University of Dhaka,